A Random Forest Approach for Bounded Outcome Variables. Issue 3 (2nd July 2020) - Weinhold, Leonie; Schmid, Matthias; Mitchell, Richard; Maloney, Kelly O.; Wright, Marvin N.; Berger, Moritz
Abstract: Random forests have become an established tool for classification and regression, in particular in high-dimensional settings and in the presence of nonadditive predictor-response relationships. For bounded outcome variables restricted to the unit interval, however, classical modeling approaches based on mean squared error loss may severely suffer as they do not account for heteroscedasticity in the data. To address this issue, we propose a random forest approach for relating a beta distributed outcome to a set of explanatory variables. Our approach explicitly makes use of the likelihood function of the beta distribution for the selection of splits during the tree-building procedure. In each iteration of the tree-building algorithm it chooses one explanatory variable in combination with a split point that maximizes the log-likelihood function of the beta distribution with the parameter estimates derived from the nodes of the currently built tree. Results of several simulation studies and an application using data from the U.S.A. National Lakes Assessment Survey demonstrate the properties and usefulness of the method, in particular when compared to random forest approaches based on mean squared error loss and parametric regression models. Supplementary materials for this article are available online.